Analysis of the Readiness of Islamic Religious Education Teachers in Implementing the Independent Curriculum in Middle Schools - Fanani, Mualfi Fahrul; Nuzula, Nafisa Ega; Gunawan, Arri Fadli (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to analyze the readiness of Islamic Religious Education teachers in implementing Kurikulum Merdeka at the Junior High School through a library research approach. Kurikulum Merdeka is the latest innovation in the Indonesian education system which focuses on flexible, innovative and student-centered learning. This research collected data from various secondary sources, including books, journal articles, research reports, and official documents related to the implementation of Kurikulum Merdeka and the readiness of PAI teachers. The results of the analysis show that PAI teachers’ readiness in implementing the Kurikulum Merdeka includes aspects of planning, implementation, and evaluation. Then, in implementing differentiated learning in the Independent Curriculum, there are six main steps which will be explained in this article. The challenges in implementing Kurikulum Merdeka in PAI learning can be from internal and external factors such as school principals, PAI teachers and other education staff, facilities and infrastructure as well as the lack of optimal synergy and cooperation between related parties. This research provides recommendations for the development of more effective training programs and educational policies that support the implementation of Kurikulum Merdeka as a whole.